Early protective role of MST1 knockdown in response to experimental diabetic nephropathy - Wu, Weihua (Am J Transl Res, 2016)
Diabetic nephropathy (DN) is a progressive kidney disease caused by the damage of capillaries in kidney’s glomeruli. Mammalian Sterile 20-like kinase 1 (MST1) has been reported to play an important role in many disease, such as diabetes, cardiac disease and ect. However, the potential role of MST1 pathway in DN has not been fully evaluated. In this study, we hypothesized that MST1 could be involved in DN, and MST1 knockdown would attenuate the DN injury in experimental diabetic nephropathy induced by streptozotocin (STZ). The sieving method was used to generate primary cultures of rat podocytes, and cultured according to the previous reports. The clinical data were analyzed for vein specimens from ESRD. Real-time quantitative PCR was used to examine the mRNA levels. Immuno-fluorescence assay was used for primary podocyte in vitro. Lectrophoretic mobility shift assay was used for DNA binding activity of NF-κB. HE staining for histological examination and western blot assay for protein expression were employed. The average GBM thickness (GBMT) was measured By using the electron microscopy. In vitro, MST1 level increased significantly in primary rat podocyte cultured in hyperglycemia condition. In vivo experiment, diabetes induced by a single STZ injection (50 mg/kg) in SD rats. Knockdown of MST1 expression by lentiviral mediated gene transfer partly reduced the proteinuria and the level of FASL, and improved the pathological changes of the diabetic kidney. In conclusion, the MST1 could be involved in DN pathogenesis and may serve as the target for development of new therapies for DN.